Pengaruh Corporate Social Responsibility Disclosure, Leverage dan Firm Size Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Bintang Kusucahyo; Devi Eka Istiana (Universitas Katolik Widya Karya Malang, 2021)
This study aims to determine the effect of Corporate Social Responsibility Disclosure, Leverage and Firm Size on the value of manufacturing companies listed on the IDX. The type of research used is explanatory research with a quantitative approach. The population in this study were manufacturing companies listed on the IDX as many as 165 companies. The sample selection used a purposive sampling method and predetermined criteria, 71 companies were selected as a sample. Secondary data sources with documentation data collection techniques, testing is done by using multiple linear regression test with a significance level of 5%. The results of the analysis show that CSR, leverage, and firm size have an effect simultaneously on firm value and partially CSR have no effect on firm value while leverage and firm size have an effect on firm value. Leverage has the most dominant effect on firm value.